Recent Developments in Correlative Super-Resolution Fluorescence Microscopy and Electron Microscopy - Jeong, Dokyung; Kim, Doory (Molecules and cells, 2022)
The recently developed correlative super-resolution fluorescence microscopy (SRM) and electron microscopy (EM) is a hybrid technique that simultaneously obtains the spatial locations of specific molecules with SRM and the context of the cellular ultrastructure by EM. Although the combination of SRM and EM remains challenging owing to the incompatibility of samples prepared for these techniques, the increasing research attention on these methods has led to drastic improvements in their performances and resulted in wide applications. Here, we review the development of correlative SRM and EM (sCLEM) with a focus on the correlation of EM with different SRM techniques. We discuss the limitations of the integration of these two microscopy techniques and how these challenges can be addressed to improve the quality of correlative images. Finally, we address possible future improvements and advances in the continued development and wide application of sCLEM approaches.